Developing criteria and indicators for responsible rural tourism in Taman Negara National Park (TNNP), Malaysia - Siow, May Ling; Zainol Abidin, Zaaba; Nair, Vikneswaran; Ramachandran, Sridar; Shuib, Ahmad (Forestry Department Peninsular Malaysia, 2011)
The tourism industry in Malaysia is being transformed from low yield to high yield income. With the launch of the Economic Transformation Programme (ETP), Malaysia is set to achieve high income nation status by the end of the decade. Rural tourism and ecotourism is growing at a phenomenal rate in Malaysia and is expected to be a major contributor to the nation's tourism receipt. Nonetheless, in the last decade, the concept of ecotourism and rural tourism has melded with mainstream tourism to lose its distinctness. Consequently, the tourism industry's growth through-out the years has created an increasing amount of stress economically, socially and environmentally. For a sustainable development of the rural tourism sector, the benefits must be equitably distributed among the private interests, public sector, tourists and local population. Criteria and indicators of sustainability that reflect the costs and benefits must be precise yet simple enough to be understood and easily implemented by field staff. The objective of this study is to develop criteria and indicators of sustainability for Taman Negara. The study uses Delphi technique to identify and develop a set of priority criteria and indicators, which is used to determine the sustainability of the development of Taman Negara National Park. The results of the study produced a set of 15 criteria and 58 indicators of sustainability which are comparable to the lists adopted by international, regional and national programs in the development of criteria and indicators. The indicators encompass the components of economic, social and environmental values associated with responsible development. These indicators will then be used in the development of a tourism barometer that will act as a national integrated tourism management system. This fundamental study plays an important role in innovating new approaches by developing indicators to holistically measure the multi-dimensional relationships between different tourism models and the linkages to local economies and environment in key natural and rural destinations in Malaysia.